2021
DOI: 10.3390/diagnostics11020244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lymphovascular Invasion on Prognosis in the Patients with Bladder Cancer—Comparison of Transurethral Resection and Radical Cystectomy

Abstract: (1) Background: This study aimed to evaluate the associations of lymphovascular invasion (LVI) at first transurethral resection of bladder (TURBT) and radical cystectomy (RC) with survival outcomes, and to evaluate the concordance between LVI at first TURBT and RC. (2) Methods: We analyzed 216 patients who underwent first TURBT and 64 patients who underwent RC at Toho University Sakura Medical Center. (3) Results: LVI was identified in 22.7% of patients who underwent first TURBT, and in 32.8% of patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 11 , 12 Although many studies have suggested the negative impact of LVI+ on prognosis, it was not included in the inclusion criteria in both clinical trials. 13 , 14 , 15 , 16 , 17 , 18 , 19 We found that more than half of the patients in this cohort had LVI+ or pN+ (very high‐risk) (Figure S4A,D ). In addition, when we simply compared LVI status in the trial‐eligible group, the median DFS was significantly worse in patients with LVI+ than in those with LVI−, which was similar to that of patients with pN+ (Figure S4B,C,E,F ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“… 11 , 12 Although many studies have suggested the negative impact of LVI+ on prognosis, it was not included in the inclusion criteria in both clinical trials. 13 , 14 , 15 , 16 , 17 , 18 , 19 We found that more than half of the patients in this cohort had LVI+ or pN+ (very high‐risk) (Figure S4A,D ). In addition, when we simply compared LVI status in the trial‐eligible group, the median DFS was significantly worse in patients with LVI+ than in those with LVI−, which was similar to that of patients with pN+ (Figure S4B,C,E,F ).…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, we speculate that the patients' LVI status may have a key role in this setting because the subanalysis of both clinical trials showed patients with T3‐4 or N+ disease had a tendency of favorable outcomes 11,12 . Although many studies have suggested the negative impact of LVI+ on prognosis, it was not included in the inclusion criteria in both clinical trials 13–19 . We found that more than half of the patients in this cohort had LVI+ or pN+ (very high‐risk) (Figure S4A,D).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Lymphovascular invasion has been reported to be independently associated with recurrence and progression of cancer cells. 27 Its presence is also considered a strong prognostic marker of tumor aggressiveness and an indicator of hidden metastasis in several malignancies, including urothelial carcinoma. 28 Tilki et al reported that lymphatic invasion was associated with nodal metastasis and poorer cancer-specific survival.…”
Section: Discussionmentioning
confidence: 99%